2013
DOI: 10.4103/1817-1737.109816
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in Saudi Arabia: A single center experience

Abstract: CONTEXT:Several international studies have described the epidemiology of pulmonary hypertension (PH). However, information about the incidence and prevalence of PH in Saudi Arabia is unknown.AIMS:To report cases of PH and compare the demographic and clinical characteristics of PH due to various causes in a Saudi population.METHODS:Newly diagnosed cases of PH [defined as mean pulmonary artery pressure >25 mmHg at right heart cauterization (RHC)] were prospectively collected at a single tertiary care hospital fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…There are no clear data regarding the true prevalence of SAPH. Rates of PH in sarcoidosis patients in tertiary centres vary between 5–20 % [ 3 , 5 , 6 ]. As a side note, the gold standard right heart catheterisation for diagnosing PH is often absent in studies, where results are based on echocardiography only.…”
Section: Epidemiologymentioning
confidence: 99%
“…There are no clear data regarding the true prevalence of SAPH. Rates of PH in sarcoidosis patients in tertiary centres vary between 5–20 % [ 3 , 5 , 6 ]. As a side note, the gold standard right heart catheterisation for diagnosing PH is often absent in studies, where results are based on echocardiography only.…”
Section: Epidemiologymentioning
confidence: 99%
“…[ 13 ] A recent publication from Saudi Arabia aimed to report cases of PH and to compare the demographic and clinical characteristics of PH due to various causes has found that the mean age at diagnosis was 55.8 (±15.8) years and there was a female preponderance of 72.3%. [ 14 ]…”
Section: Prevalencementioning
confidence: 99%
“…Another report from Saudi Arabia described the distribution of PH in 112 patients diagnosed by RHC found that 10.7% belonged to PAH, 6% to PH due to left heart disease, 65% to PH due to lung diseases, 3.5% to chronic thromboembolic PH (CTEPH), and 14.2% related to WHO group V diseases. 56 However, this center is recognised as the national center of interstitial lung disease and referral bias can explain the high prevalence of PH due to lung disease in this cohort.…”
Section: Prevalence Of Pulmonary Hypertension In the Developing Worldmentioning
confidence: 88%